Significance of MEF2C and RUNX3 Regulation for Endochondral Differentiation of Human Mesenchymal Progenitor Cells - Dreher, Simon I.; Fischer, Jennifer; Walker, Tilman; Diederichs, Solvig; Richter, Wiltrud (Frontiers in Cell and Developmental Biology, 2020)
Guiding progenitor cell development between chondral versus endochondral pathways is still an unachieved task of cartilage neogenesis, and human mesenchymal progenitor cell (MPC) chondrogenesis is considered as a valuable model to better understand hypertrophic development of chondrocytes. Transcription factors Runx2, Runx3 and Mef2c play prominent roles for chondrocyte hypertrophy during mouse development, but little is known on the importance of these key fate-determining factors for endochondral development of human MPC. Aim of this study was to unravel the regulation of RUNX2, RUNX3 and MEF2C during MPC chondrogenesis, the pathways driving their expression and the downstream hypertrophic targets affected by their regulation. RUNX2, RUNX3 and MEF2C gene expression was differentially regulated during chondrogenesis of MPC, but remained low and unregulated when non-hypertrophic articular chondrocytes were differentiated under the same conditions. RUNX3 and MEF2C mRNA and protein levels rose in parallel to hypertrophic marker upregulation but, surprisingly, RUNX2 gene expression changed only by trend and RUNX2 protein remained undetectable. While RUNX3 expression was driven by TGF-β- and BMP-signaling, MEF2C responded to WNT-, BMP- and Hedgehog-pathway inhibition. MEF2C but not RUNX3 levels correlated significantly with COL10A1, IHH and IBSP gene expression when hypertrophy was attenuated. IBSP was a downstream target of RUNX3 and MEF2C but not RUNX2 in SAOS-2 cells, underlining the capacity of RUNX3 and MEF2C to stimulate osteogenic marker expression in human cells. Conclusively, RUNX3 and MEF2C appeared more important than RUNX2 for human endochondral MPC chondrogenesis. Pathways altering the speed of chondrogenesis (FGF, TGF-β, BMP) affected RUNX2 or RUNX3, while pathways changing hypertrophy (WNT, PTHrP/HH) regulated mainly MEF2C. Taken together, reduction of MEF2C levels is a new goal to shift human cartilage neogenesis towards the chondral pathway.